CÂTEVA PROBLEME ALE MOTIVAŢIEI ÎN FORMAREA COMPETENŢELOR COMUNICATIVE LA ORELE DE LIMBĂ ROMÂNĂ PENTRU ALOLINGVI - USM ADMIN (Moldova State University, 2007)
The study deals with a major problem of the motivation in developing communicative skills in language studying. There is an explanation for motivation as a term and the description of its constituents. The lack of this major factor makes difficult the process of learning Romanian as the official language in Republic of Moldova for foreign citizens and even the teachers efforts to teach Romanian to groups students speaking other languages are insignificant or fruitless. The Council of Europe has formulated the priorities concerning the study of national languages but these are not yet available in our country. The opportunity of total integration of the students in the social and economical life of Republic must be the perfect motivation in studying Romanian.